Euglenozoan kleptoplasty illuminates the early evolution of photoendosymbiosis - Karnkowska, Anna; Yubuki, Naoji; Maruyama, Moe; Yamaguchi, Aika; Kashiyama, Yuichiro; Suzaki, Toshinobu; Keeling, Patrick J; Hampl, Vladimír; Leander, Brian S (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Kleptoplasts (kP) are distinct among photosynthetic organelles in eukaryotes (i.e., plastids) because they are routinely sequestered from prey algal cells and function only temporarily in the new host cell. Therefore, the hosts of kleptoplasts benefit from photosynthesis without constitutive photoendosymbiosis. Here, we report that the euglenozoan Rapaza viridis has only kleptoplasts derived from a specific strain of green alga, Tetraselmis sp., but no canonical plastids like those found in its sister group, the Euglenophyceae. R. viridis showed a dynamic change in the accumulation of cytosolic polysaccharides in response to light-dark cycles, and 13C isotopic labeling of ambient bicarbonate demonstrated that these polysaccharides originate in situ via photosynthesis; these data indicate that the kleptoplasts of R. viridis are functionally active. We also identified 276 sequences encoding putative plastid-targeting proteins and 35 sequences of presumed kleptoplast transporters in the transcriptome of R. viridis. These genes originated in a wide range of algae other than Tetraselmis sp., the source of the kleptoplasts, suggesting a long history of repeated horizontal gene transfer events from different algal prey cells. Many of the kleptoplast proteins, as well as the protein-targeting system, in R. viridis were shared with members of the Euglenophyceae, providing evidence that the early evolutionary stages in the green alga-derived secondary plastids of euglenophytes also involved kleptoplasty.
Keywords: plastidy; symbióza; Photosynthesis; euglenozoa; Chlorophyta; Phylogeny; horizontal gene transfer; transkriptom; Eukaryota; Transcriptome; plastid evolution; kleptoplasty; Symbiosis; fotosyntéza; Plastids; fylogeneze; endosymbiosis